Theoretical and applied aspects of industrial and competition policy harmonization - I. F. Bogatyrev (Publishing House of the State University of Management, 2021)
The relevance of studying the harmonization of industrial policy with other types of economic policy is determined, the structure of industrial policy is presented, the main directions of harmonization are noted. The external harmonization of industrial policy is analysed in detail on the example of competition policy. The main aspects of each of the policies are considered, their main differences are noted. Attention is focused on their possible mutual complementarity in order to achieve a higher positive effect from the implementation of each. The current state of harmonization in Russia is considered, in particular, the conclusion is made about the dominance of industrial policy over competition. The main problems of harmonization are highlighted, including the discrepancy between pre-set goals in industrial policy and the final results. The problem of small and medium-sized businesses in industry is identified, the factors hindering the development of subjects of these categories are formulated.